Utilização de substratos alternativos na produção de Tagetes patula em vaso - Araújo, Daniel Barbosa (2016)
The accumulation and inadequate disposal of waste are responsible, among the main factors, for damage to the environment through soil contamination and proliferation of transmitters of disease agents. The use of organic waste in the form of compounds and agricultural substrates can be an alternative to reduce those impacts and costs for producers who use these inputs in the production of seedlings and potted ornamental species. The objective of this study, is to evaluate the products waste utilization of fruits and vegetables, in substrates based waste agro-industrial, irrigated with nutrient solution and water, in production of Tagetes patula in vase. The experiment was conducted in a greenhouse, using a completely randomized experimental design in subdivided plots, two main treatments (irrigation with nutrient solution and water), six secondary treatments, consisting of 5 substrates based on agro-industrial residues (green coconut coir, wax carnaúba straw and soil hydromorphic), formulated with increasing proportions of organic compound (OC) (10, 20, 30, 40 and 50%) and 1 commercial substrate used as control, in 4 replicates (repetitions). Each experimental unit consisted of 3 plants. All variables were submitted to F-test, and in case of significance, the Tukey test (p<0.05) was used to compare means. To compare the control treatment (comercial substrate) with the alternative substrates, we used Dunnet’s test (p<0.05). For the evaluation of gait and dynamics of nutrients over time, we used the data of the produced plants, only in substrate with 30% in OC, irrigated with nutrient solution, adjusting the regression equations after the variance analysis, being considered independent variable the age of the plant. Alternative substrates based agro-industrial and agricultural wastes are more suitable in the production of Tagetes patula when irrigated with water and formulated with 47% OC, or when irrigated with nutrient solution and 24% OC, which are 93% and 89%, respectively more economic that the comercial substrate. The decreasing order of nutrients accumulated in plant Tagetes patula (mg plant-1): N = 101.9; K = 92.0; Ca = 23.1; P = 14.5, Mg = 10.9; S = 8.6; (μg planta-1) of: Fe = 271.6; Mn = 197.3; B = 80.0; = 77.3 Zn and Cu = 23.2. The greatest period requirement of nutrients in tissues and comprised between 0-5 days after transplanting.